Management Guidelines for Metal-on-metal Hip Resurfacing Arthroplasty: A Strategy on Followup - Nakano, Naoki (Indian J Orthop, 2017)
Despite the initial promise of metal-on-metal (MoM) implants as the ideal bearing surface for hip replacements and resurfacings, high short term failure rates due to an adverse reaction to metal debris (ARMD) have led to a dramatic reduction in the number of MoM implants used in the modern era. With over one million patients worldwide having undergone hip operations utilizing a MoM bearing surface, the long term outcomes for such patients remains unknown, and there is much debate as to the most effective management of these patients. Although several regulatory bodies have released guidelines on the management of patients with MoM hips, these recommendations remain open to interpretation, and the most effective management for these patients remains unclear. The aim of this review is to compare the current guidelines for managing patients with MoM hips and also to discuss established ARMD risk factors, evidence regarding the optimum management for patients with MoM hips, and the indications for revision surgery. Furthermore, although specialized laboratory tests and imaging can be used to facilitate clinical decision making, over-reliance on any single tool should be avoided in the decision making process, and surgeons should carefully consider all findings when determining the most appropriate course of action.